Suppressing delaminations in composites across a range of loading modes - M’membe, Beene; Yasaee, Mehdi; Hallett, Stephen R.; Partridge, Ivana K. (Cranfield University, 2017)
This study presents two means of achieving high fracture toughness throughout the entire mixed Mode I/II test range, using customised placement of composite and metal Z-pins in hybrid arrays, and novel hybrid metal/composite Z-pins. The study shows that hybrid arrays that contain an equal number of composite and metal Z-pins exhibit a notable increase in the apparent fracture toughness in Mode II compared to 100% composite pins, while maintaining adequate Mode I performance. Hybrid metal/composite Z-pins, which consist of a composite exterior and a metal core have been shown to offer a single Z-pin solution for high fracture toughness under mixed Mode I/II loads without compromising either Mode I or Mode II performance of individual composite or metal Z-pins respectively. The composite exterior of the hybrid Z-pin ensures high resistance to pull-out failure, whilst the metal core guarantees high energy absorption at high mixed mode load angles via plastic deformation.
Keywords: Fracture Toughness; Z-pins; Through thickness Reinforcements